2018
DOI: 10.3389/fgene.2018.00279
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Diversity and Clustering Analysis for Chinese Dongxiang Group With 30 Autosomal InDel Loci Simultaneously Analyzed

Abstract: In comparison with the most preferred genetic marker utilized in forensic science (STR), insertion/deletion analysis possesses further benefits, like absence of stutter peak, low mutation rate, and enabling mixed stain analysis. At present, a total of 169 unrelated healthy Dongxiang individuals dwelling in Dongxiang Autonomous county of Gansu province were recruited in our study to appraise the forensic usefulness of the panel including 30 autosomal diallelic genetic markers. The insertion allele frequencies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…To comprehensively explore the patterns of genetic affinity between our studied populations and worldwide reference populations, we merged our newly obtained population data with those of 61 worldwide populations. The final database used in the population comparison study included 6483 East Asian individuals from 38 populations [4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], 494 South Asians from three populations [27][28][29], 300 Vietnamese of Southeast Asia [30], 194 West Asians from two populations [31], 621 African individuals from five populations [27,30,32], 984 European individuals from eight populations [4,[31][32][33][34][35] and 1 071 South Americans from eight populations [36,38]. The detailed geographical regions and population sizes of these included populations are submitted in Supplementary Table S1.…”
Section: Reference Databasementioning
confidence: 99%
“…To comprehensively explore the patterns of genetic affinity between our studied populations and worldwide reference populations, we merged our newly obtained population data with those of 61 worldwide populations. The final database used in the population comparison study included 6483 East Asian individuals from 38 populations [4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], 494 South Asians from three populations [27][28][29], 300 Vietnamese of Southeast Asia [30], 194 West Asians from two populations [31], 621 African individuals from five populations [27,30,32], 984 European individuals from eight populations [4,[31][32][33][34][35] and 1 071 South Americans from eight populations [36,38]. The detailed geographical regions and population sizes of these included populations are submitted in Supplementary Table S1.…”
Section: Reference Databasementioning
confidence: 99%
“…To gain an overview of the genetic similarities and differences between our studied populations and 56 global populations (East Asian [8][9][10][11][12][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], West Asian [36,37], European [33,[37][38][39][40][41][42], American [43][44][45], African [23,46]), we conducted population comparisons along continental divisions through a series of analyses. In the cluster heatmap (Supplementary Figure S1), the HLD101, HLD114, HLD39, HLD48 and HLD111 loci showed high deletion frequencies in most East Asian populations, while the HLD118, HLD99, HLD64 and HLD81 loci showed low deletion frequencies in these groups.…”
Section: Genetic Differentiation Along Continental Divisionsmentioning
confidence: 99%
“…Chinese populations [8][9][10][11][12]21,22,[24][25][26][27][28][29][30][31][32][33]. Supplementary Figure S4 presents the cluster heatmap of deletion allele frequencies among the 30 populations, and three primary clusters (I, II and III) were easily distinguished.…”
Section: Genetic Differentiation Along Ethnic and Linguistic Divisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they could also serve as ancestry-informative markers (AIMs) for characterizing population substructure and performing biogeographical origin analyses [5][6][7]. In recent years, more and more studies have found that InDels could be useful in human identification [1], mixed stain identification [8], and so on.…”
Section: Introductionmentioning
confidence: 99%